Words from the edge: A postmodern reflection on Coolie Verner and the black book - Roger Boshier (Adult Education Research Conference, 1995)
Coolie Verner was a Virginian patrician who made significant contributions to the black book. He lived on the edge of society where he yearned for love that invariably slipped away. This impeded his ability to complete projects and, for him, the black book turned into an "unmitigated disaster".